2007
DOI: 10.1016/j.chembiol.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

LMP2-Specific Inhibitors: Chemical Genetic Tools for Proteasome Biology

Abstract: The immunoproteasome, having been linked to neurodegenerative diseases and hematological cancers, has been shown to play an important role in MHC class I antigen presentation. However, its other pathophysiological functions are still not very well understood. This can be attributed mainly to a lack of appropriate molecular probes that can selectively modulate the immunoproteasome catalytic subunits. Herein, we report the development of molecular probes that selectively inhibit the major catalytic subunit, LMP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(141 citation statements)
references
References 50 publications
5
130
0
6
Order By: Relevance
“…Bortezomib, which targets the constitutive proteasome and immunoproteasome, is the first clinically approved proteasome inhibitor for relapsed and/or refractory myeloma and mantle cell lymphoma (34). Recently, novel proteasome inhibitors preferentially targeting subunits of the immunoproteasome were described (22,(35)(36)(37)). An LMP2-specific inhibitor attenuated proliferation in myeloma patient samples and other hematologic malignancies, although the chymotrypsin-like activity associated with the subunits b5 and b5i was also reduced at the concentrations used (37).…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib, which targets the constitutive proteasome and immunoproteasome, is the first clinically approved proteasome inhibitor for relapsed and/or refractory myeloma and mantle cell lymphoma (34). Recently, novel proteasome inhibitors preferentially targeting subunits of the immunoproteasome were described (22,(35)(36)(37)). An LMP2-specific inhibitor attenuated proliferation in myeloma patient samples and other hematologic malignancies, although the chymotrypsin-like activity associated with the subunits b5 and b5i was also reduced at the concentrations used (37).…”
Section: Discussionmentioning
confidence: 99%
“…The precise activity conferred by b1i incorporation appears controversial in reporter assays, potentially due to co-incorporation of b2i (77). However, a b1i-specific inhibitor reduces chymotrypsin-like activity and hydrophobic substrate preference of b1i is supported by protein crystallography (97,103). Similar to b2 and b5, subunits b2i and b5i preferentially cleave polypeptides after alkaline and hydrophobic amino acids, respectively (68,103).…”
Section: S Proteasome Inhibitionmentioning
confidence: 84%
“…Resistance is overcome, at least in part, by carfilzomib (90), a peptidyl-epoxyketone that targets similar proteasome activities such as bortezomib, but binds irreversibly to proteolytic sites (122). Lessening adverse effects may be achieved by targeting those proteasome subpopulations that are most abundant in target cells (97,121,151). For example, the inhibitors IPSI-001 and PR-957 preferentially target inducible proteasome subunits (122), such as b5i (103).…”
Section: S Proteasome Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a TBSprotected compound showed excellent biological activity. 6 Direct comparison of catechol 6c and dimethoxy 5c revealed that catechol moiety is essential to exhibit anti-proliferative activity. Only 4-chloro analog 5i retained activity among dimethoxy derivatives, thus we hypothesize it could have different binding mode.…”
mentioning
confidence: 99%